Malignant DFFB isoform switching promotes leukemia survival in relapse pediatric T‐cell acute lymphoblastic leukemia - Sabina Enlund; Indranil Sinha; Amanda Ramilo Amor; Shahrzad Shirazi Fard; Ekaterina Pokrovskaja Tamm; Qingfei Jiang; Vanessa Lundin; Anna Nilsson; Frida Holm (eJHaem, 2023)
Abstract With modern treatment most children with acute lymphoblastic leukemia (ALL) survive without relapse. However, for children who relapse the prognosis is still poor, especially in children with T‐cell phenotype (T‐ALL) and remains the major cause of death. The exact mechanism of relapse is currently not known. While contribution of RNA processing alteration has been linked to other hematological malignancies, its contribution in pediatric T‐ALL may provide new insights. Almost all human genes express more than one alternative splice isoform. Thus, gene modulation producing a diverse repertoire of the transcriptome and proteome have become a significant molecular marker of cancer and a potential therapeutic vulnerability. To study this, we performed RNA‐sequencing analysis on patient‐derived samples followed by splice isoform‐specific PCR. We uncovered a distinct RNA splice isoform expression pattern characteristic for relapse samples compared to the leukemia samples from the time of diagnosis. We also identified deregulated splicing and apoptosis pathways specific for relapse T‐ALL. Moreover, patients with T‐ALL displayed pro‐survival splice isoform switching favoring pro‐survival isoforms compared to normal healthy stem cells. Cumulatively, pro‐survival isoform switching and DFFB isoform regulation of SOX2 and MYCN may play a role in T‐ALL proliferation and survival, thus serving as a potential therapeutic option.